Conservative Medical Management of a Tracheal Perforation after Blunt Trauma in a Patient with SARS-CoV-2 - Mateo Zuluaga-Gómez; Daniel González-Arroyave; Carlos M. Ardila (Case Reports in Medicine)
This article reports the case of a woman with tracheal perforation due to closed neck trauma and the presence of SARS-CoV-2. The physical examination revealed subcutaneous emphysema in zone II of the neck. The tomography revealed an anterior and proximal tracheal lesion, a 2-mm solution of continuity of the anterior infraglottic airway in the proximal third with subcutaneous emphysema and a decrease in the diameter of the airway at the level of the glottis. The PCR result for SARS-CoV-2 was positive. The medical procedure consisted of orotracheal intubation to guarantee the safety of the airway, in addition to close surveillance in the intensive care unit and constant monitoring of vital signs. In tracheal perforation due to closed neck trauma, it is recommended to evaluate the clinical parameters periodically, including the stability of respiration and subcutaneous emphysema.